The child survivor : healing developmental trauma and dissociation - Silberg, Joyanna L. (New York, NY : Routledge, 2021)
"In the second edition of Joyanna Silberg's classic The Child Survivor, practitioners will find practical management tools that are backed up by recent scientific advances in neurobiology. The new edition addresses the impact of the Covid-19 pandemic on children, provides tips for working with traumatized children in telehealth, and explains the ten biggest mistakes therapists make. A new chapter on organized abuse explains how children victimized by sex trafficking perpetrators, abusive cults, and online predators can respond well to therapy. The new edition also includes updated discussion of new brain imaging research and theoretical contributions from Sandra Wieland, Frances Waters, Na'ama Yehuda, Martha Straus, and others. Clinicians on the front lines of treatment will come away from the book with an arsenal of therapeutic techniques that they can put into practice right away, limiting the need for restrictive hospitalizations or out-of-home placements for their young clients"--
Keywords: Dissociative disorders in children; Dissociative disorders -- Treatment; Psychic trauma -- Treatment; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Mental Health